The Principle of Good-Neighbourliness in International Nuclear Law - Gadkowski, Tomasz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The paper is an English translation of Zasada dobrego sąsiedztwa w międzynarodowym prawie atomowym by Tadeusz Gadkowski, published originally in Polish in 1997. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Department of Public International Law” devoted to the achievements of the representatives of the Poznań studies on international law.